A neuronal β subunit (KCNMB4) makes the large conductance, voltage- and Ca(2+)-activated K(+) channel resistant to charybdotoxin and iberiotoxin - Meera, Pratap (The National Academy of Sciences, 2000)
Large conductance voltage and Ca(2+)-activated K(+) (MaxiK) channels couple intracellular Ca(2+) with cellular excitability. They are composed of a pore-forming α subunit and modulatory β subunits. The pore blockers charybdotoxin (CTx) and iberiotoxin (IbTx), at nanomolar concentrations, have been invaluable in unraveling MaxiK channel physiological role in vertebrates. However in mammalian brain, CTx-insensitive MaxiK channels have been described [Reinhart, P. H., Chung, S. & Levitan, I. B. (1989) Neuron 2, 1031–1041], but their molecular basis is unknown. Here we report a human MaxiK channel β-subunit (β4), highly expressed in brain, which renders the MaxiK channel α-subunit resistant to nanomolar concentrations of CTx and IbTx. The resistance of MaxiK channel to toxin block, a phenotype conferred by the β4 extracellular loop, results from a dramatic (≈1,000 fold) slowdown of the toxin association. However once bound, the toxin block is apparently irreversible. Thus, unusually high toxin concentrations and long exposure times are necessary to determine the role of “CTx/IbTx-insensitive” MaxiK channels formed by α + β4 subunits.